A nation upon the ocean sea: Portugal's Atlantic diaspora and the crisis of the Spanish Empire, 1492-1640 - Studnicki-Gizbert, Daviken (Oxford University Press, 2007)
1. Portuguese nation and Spanish empire in the sixteenth century -- 2. Settling upon the seas : a maritime community in movement and formation -- 3. "Cada casa, un mundo" : the domestic foundation of a trading community -- 4. A vast machine : the nation's Atlantic trading networks -- 5. Representing the market : from day-to-day experience to the literature of commercial reform -- 6. The nation unraveled